ORGANIZATION OF STUDENT WORK IN HOMEWORK PROCESSES (Pedagogy of Higher and Secondary Education, 2000)
The optimum system of way in the process of doing the hometasks, which depends on the correct organization in time and order of making tasks and also the alternation the periods of work and relaxation has been grounded in this article.